2006
DOI: 10.1080/00015458.2006.11679993
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Pseudocyst Presenting as Acute Abdomen during Pregnancy

Abstract: Pseudocysts of the adrenal gland are rare lesions, which are usually discovered as incidental findings. Since they are in the majority of cases non-functioning, they become symptomatic only when they are complicated with rupture, haemorrhage or infection. We present a case of a 28-year-old woman in the 26th gestational week, who developed an acute abdomen due to a haemorrhagic pseudocyst of the left adrenal. The patient was submitted to left adrenalectomy. The described case is the third reported case of cysti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…Although percutaneous drainage was tried as a fi rst-line treatment in two patients, it was unsuccessful and complete excision was subsequently necessary. 20,21 After complete excision, the pregnancy resulted in normal delivery in fi ve patients 15,18,20,21,23 and in preterm delivery in one. 22 Therapeutic termination was required in three patients: for fear of fetal teratogenicity because of exposure to radiation and drugs used for resuscitation in two, 6 and because of maternal recurrent pulmonary emboli resistant to anticoagulant therapy in one.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Although percutaneous drainage was tried as a fi rst-line treatment in two patients, it was unsuccessful and complete excision was subsequently necessary. 20,21 After complete excision, the pregnancy resulted in normal delivery in fi ve patients 15,18,20,21,23 and in preterm delivery in one. 22 Therapeutic termination was required in three patients: for fear of fetal teratogenicity because of exposure to radiation and drugs used for resuscitation in two, 6 and because of maternal recurrent pulmonary emboli resistant to anticoagulant therapy in one.…”
Section: Discussionmentioning
confidence: 98%
“…19 Moreover, three patients were operated on twice because of the diffi culties in identifying the responsible lesion that originated in the retroperitoneum (Table 1). 17,18,23 Papaziogas et al recently reported fi nding a retroperitoneal tumor at an emergency exploratory laparotomy, performed after signs of acute abdomen and circulatory shock developed in their patient. 23 Since there were no signs of active bleeding within the peritoneal cavity, the abdomen was closed and the nature of the tumor was investigated.…”
Section: Ovarian Veinmentioning
confidence: 98%
See 3 more Smart Citations